2019
DOI: 10.1038/s41564-019-0641-0
|View full text |Cite
|
Sign up to set email alerts
|

Diet-derived galacturonic acid regulates virulence and intestinal colonization in enterohaemorrhagic Escherichia coli and Citrobacter rodentium

Abstract: Enteric pathogens sense the complex chemistry within the gastrointestinal (GI) tract to efficiently compete with the resident microbiota and establish a colonization niche. Here we show that enterohemorrhagic E. coli (EHEC), and its surrogate murine infection model Citrobacter rodentium, sense galacturonic-acid to initiate a multi-layered program towards successful mammalian infection. Galacturonic-acid utilization as a carbon source aids the initial pathogen expansion. The main source of galacturonic-acid is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Sugar acids have been extensively implicated in bacterial colonization and virulence. For example, E. coli fecal isolates unable to utilize D-gluconate are defective in intestinal colonization (Sweeney et al, 1996), metabolism of D-galactarate and D-glucarate enables postantibiotic expansion of Salmonella enterica serovar Typhimurium in the gut (Faber et al, 2016), enterohemorrhagic E. coli and Citrobacter rodentium use diet-derived D-galacturonic acid for intestinal colonization and as a signal to induce synthesis of virulence factors (Jimenez et al, 2020), and D-galactonate metabolism is suggested to enable the growth of E. coli strains in human urine and mammalian gut, and of Salmonella enterica strains in egg white, macrophages, and soft-rotted leaves (Baron et al, 2017;Eriksson et al, 2003;Goudeau et al, 2013;Lescat et al, 2016;Roos et al, 2006).…”
mentioning
confidence: 99%
“…Sugar acids have been extensively implicated in bacterial colonization and virulence. For example, E. coli fecal isolates unable to utilize D-gluconate are defective in intestinal colonization (Sweeney et al, 1996), metabolism of D-galactarate and D-glucarate enables postantibiotic expansion of Salmonella enterica serovar Typhimurium in the gut (Faber et al, 2016), enterohemorrhagic E. coli and Citrobacter rodentium use diet-derived D-galacturonic acid for intestinal colonization and as a signal to induce synthesis of virulence factors (Jimenez et al, 2020), and D-galactonate metabolism is suggested to enable the growth of E. coli strains in human urine and mammalian gut, and of Salmonella enterica strains in egg white, macrophages, and soft-rotted leaves (Baron et al, 2017;Eriksson et al, 2003;Goudeau et al, 2013;Lescat et al, 2016;Roos et al, 2006).…”
mentioning
confidence: 99%
“…Many studies have pointed toward important roles for distinct dietary constituents in manipulating virulence and the progression of disease by A/E pathogens. Dietary fiber has been directly implicated in affecting disease severity in EHEC ( 29 ), while supplementation of diet with phytonutrients (plant extracts) ( 30 ) and pectin ( 31 ) reduce the severity of infection by Citrobacter rodentium —a natural pathogen of mice that employs a LEE-encoded type 3 secretion system similar to EHEC for intestinal colonization. Fucose has also been shown to repress expression of the LEE in EHEC via the fucose two-component sensor FusKR ( 32 ); however, the main source of free fucose is thought to be cleavage of intestinal mucins by commensal bacteria, while the contribution of diet to free fucose levels in the gut has been poorly studied ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the results of previously cited studies, Jimenez et al. (2019) discussed the role of diet‐derived GalA in the infection and gut colonization of two enteric pathogens, Enterohaemorrhagic Escherichia coli and Citrobacter rodentium . Saccharolytic strains of gut microbiota can break down HG pectin into GalA oligomers or residues, which were able to promote pathogen expansion in the initial stage of infection and enhance E. coli growth (Chang et al., 2004; Fabich et al., 2008).…”
Section: Regulation Of Ibd By Various Pectic Substancesmentioning
confidence: 94%
“…Saccharolytic strains of gut microbiota can break down HG pectin into GalA oligomers or residues, which were able to promote pathogen expansion in the initial stage of infection and enhance E. coli growth (Chang et al, 2004;Fabich et al, 2008). According to Jimenez et al (2019), sensing of GalA regulated through ExuR transcription factor could aid the pathogen to initiate infectious colitis. However, the concentration of GalA after fermentation is hard to control and the effects of parental pectins on this system were not determined.…”
Section: Galacturonan Backbone Of Hg Pectinmentioning
confidence: 99%